Ekonomi Kreatif dalam Islam: Tinjauan Maqashid Syariah Terhadap Pemanfaatkan Kain Sisa Jahitan di Kota Langsa - M. Yahya; Aning Cipta Rahayu; Muhazir Muhazir (ITB AAS INDONESIA Surakarta, 2022)
It has become a habit for tailors to make the remaining fabric of the stitches to be managed so that it has economic value and benefits. The paradigm that emerged for tailors is that the leftover fabric is certainly no longer needed by its customers, so the idea arises to recycle it so that it can be used. This paper aims to analyze the use of leftover fabric from the maqashid sharia point of view. This research resulted from an empirical study with a sociological normative approach. Data were obtained from interviews with tailors and customers in Langsa City. The results indicate that tailors have a perception of the rest of the sewing fabric that can be used even without the owner's permission, this perception departs from the understanding that so as not to be redundant, it is appropriate to use the remaining fabric. When looking at the normative aspect of fiqh muamalah, there is a prohibition on taking other people's belongings without the permission of the owner. However, in a sociological context with the maqashid sharia approach, this can be tolerated because in general, the leftover fabric can be grouped into useless items (garbage), so that it is permissible to recycle waste to make it more useful. But it would be better for the tailors to ask permission from the owner of the cloth to use the rest of the cloth.